Incremental Innovation as Sustainable Development of Agriculture : Case Study of Farmer’s Card (Kartu Tani) - Nurdin, Ali; Lubis, Muharman; Amril, Salsabila Zahrani; Prayoga, Danar; Muhdiantini, Cindy; Paramita, Paramita (Universitas Galuh, 2024)
The agricultural technology and system have contributed positively to the expansion of agricultural development in Indonesia. While the increased output benefits the majority of farmers, a subset experiences stagnation or even loss. Weather, fertilizer quality and availability, price, and marketing, among other variables, significantly impact the performance of a farm. The research object, Kartu Tani's system, was introduced in Indonesia in 2017; however, it only receives a one-third benefit from users, resulting in a twenty percent lower profit margin when compared to comparable products that use alternative fertilizers. The efficacy of digitization may be compromised in the absence of user readiness. Strategies (system role simplification) and business model approaches (system role modification) are methods for optimizing the kartu tani's system. By capitalizing on the momentum of digitalization and collaboration, significant innovations will be put forth. As a means of attracting users who are able to allocate greater financial resources, Kartu Tani has emerged as a pioneering advantage in agricultural systems.